Effect of SiC Particle Incorporated Dielectric Medium on Electrical Discharge Machining Behavior of AA6061/B4Cp/SiCp AMCs - Johny Khajuria; N. Nagabhooshanam; Pankaj Sharma; Atul Kumar; Santosh Kumar Sahu; Peyyala Sree Devi; Kuma Gowwomsa Erko (Advances in Materials Science and Engineering)
In this work, it was observed that using motor oil as the dielectric fluid when producing AA6061/SiCp/B4Cp hybrid composites provided wealth from waste. In these studies, modifications in silicon carbide (SiC) concentration, electrode (copper and brass), current, pulse time, and reinforcing weight percentage were tested. Surface roughness and machined hardness are measured and reported for each removed piece of the material. The bridging effect of silicon carbide particles raised the material removal rate (MRR), while a thorough dielectric fluid flush enhanced the Ra value. On the machined topography, the oil carbon content left dark smudges. Machining performance is superior to that of copper electrode-processed specimens. The MRR, TWR, and Ra all rise as the discharge current and pulse duration increase. Because there is no remelted layer, composites with low machining surface hardness had better finishes. The parameters were optimized using the TOPSIS approach, and it was observed that the efficiency of machining was enhanced by utilizing engine oil by the concentration of 4 gl−1. Moreover, during machining, optimized parameters like pulse on time 36 seconds, current 4 Amps, and also a brass electrode.